(untitled) (Damascus University Journal for legal sciences, 2024)
The covid-19 pandemic was an exceptional circumstance that threatened the health and life of humanity around the word. This search tried to find an answer to the most imprtant inquiry in the last days which is "Can the government restrict individual liberties and rights to stop the spread of COVID-19? " Actully, The governments were forced to addressed by firm measures to curb the pandemic from spread to preserve public health In this exceptional circumstance, and these measures had a direct impact on the freedoms of citizens. So, the governments had to obligated to find a balance between commitment the constitution and respecting the international human rights standards from one side, and imposing restrictions related to stopping the virus from the other side. This search discussed the legal basis adopted by governments for their policies and procedures, and the idea of expanding their powers during the covid-19 crisis.